Parasitic Helminthes of Native Chickens in the Central Part of Tailand - Arkom Sangvaranond (Agriculture and Natural Resources, 1994)
Studies on prevalence of parasitic helminthes by post mortem examinations of 214 carsasses of adult native chickens (age : 8 months – 1.5 years; 111 males and 103 females) which collected from provinces in the central part of Thailand, during June to November 1993, revealed the following species of parasitic helminthes; flukes (Trematodes) 3 species, Echinostoma revolutum (1.9%) Catatropis verrucosa (0.9%), and Prosthogonimus pellucidus (12.5%); tapeworms (Cestodes) 6 species, Raillietina tetragona (20.1%), Raillietina echinobothrida (66.8%), Raillietina cesticillus (8.4%), Cotugnia digonophora (2.3%), Amoebotaenia cuneata (12.2%) and Hymenolepis carioca (37.9%); roundworms (Nematodes) 5 species, Ascaridia galli (21.5%), Heterakis gallinarum (68.7%), Tetrameres fissispina (43.8%), Gongylonema ingluvicola and Oxyspirura mansoni. Character of infestation and habitat of these helminghes (especially of cestode parasites) were also reported in this study.